Hemolytic uremic syndrome outbreak in Turkey in 2011 - (:unkn) unknown (TURKISH J PEDIATRICS, 2013)
The aim of this retrospective multicenter study was to define the epidemiological and clinical features and prognostic factors of the first diarrhea-related hemolytic uremic syndrome (D+HUS) outbreak in Turkey in 2011. All pediatric nephrology centers in Turkey were asked about D+HUS patients via e-mail. Seventy D+HUS patients (median age: 5.7 years) participated. The seasonal peak was around the 7th, 8th and 9th months with 44 cases, centered in the east Marmara region. No causative agent could be identified. The rate of neurological complications and mortality was 21.4% and 4.2%, respectively. Eculizumab was used in four cases. Two of them had severe neurological complications despite plasma exchange. Elevated polymorphonuclear leukocyte count during hospital admission was the predictor of both severe disease and poor outcome. Duration of prodrome was the predictor of poor outcome (p<0.05). In conclusion, the median age of the affected children was greater than in the previous reports, while clinical features and outcome were similar.
Keywords: hemolytic uremic syndrome; diarrhea-related; outbreak; children; epidemiology; eculizumab; E.-COLI O104/H4; ESCHERICHIA-COLI; ECULIZUMAB; GERMANY